Coordination strategy-induced selective C–H amination of 8-aminoquinolines. Issue 50 (7th June 2017) - Yi, Hong; Chen, Hong; Bian, Changliang; Tang, Zilu; Singh, Atul K.; Qi, Xiaotian; Yue, Xiaoyu; Lan, Yu; Lee, Jyh-Fu; Lei, Aiwen
Abstract : Using coordination-strategy, we realized a selective C–H amination of 8-aminoquinolins on the C5 position employing azoles as amines sources. Abstract : In this study, we broke through the directing function of the amide group. The coordination interaction between metal and directing-group enhanced the reactivity of the substrate. Using this strategy, we realized the selective amination of 8-aminoquinolines at the C5 position via employing azoles as the source of amine. Various kinds of 8-aminoquinolines and different substituted azoles were compatible to afford the corresponding C–N coupling products.